Exploring the space economy: The present and future of capitalism beyond our planet - Rainer Zitelmann (Institute of Economic Affairs (IEA), 2025)
The Space Economy is defined by the OECD as 'activities and use of space resources that create value and benefits for humanity in the course of exploring, researching, understanding, managing and utilizing space.' * The value of the Space Economy in the early 2020s was somewhere between 370 billion and 470 billion (depending on how you count it), with satellite navigation and communication accounting for the lion's share. It employed around 400,000 people. These figures are projected to grow rapidly. * The Space Economy is no longer primarily about government research and defence projects. Private enterprise and commercial projects now account for the bulk of it. * One of the most important consequences of the growing involvement of private companies has been the dramatic reduction in costs, especially of satellite production and rocket launches. Under the old, state-centric model, there was little incentive for cost-cutting innovation, since government agencies would simply pick up the tab whatever the cost. * The old state-dominated Space Economy was often overtly politicised, with too many contracts awarded on nakedly political grounds (e.g. biased towards swing states and election years), and abrupt swings in priorities after changes in government. * Limited forms of asteroid mining, i.e. the extraction of valuable resources from asteroids, are already technologically 5 feasible, and may become economically feasible too in the future. This might require some legal clarifications, namely, defining some form of private property rights in outer space. * In the West, the Space Economy is being held back by a form of 'Space NIMBYism', where opponents use public consultations to weaponise regulatory constraints. As one publication puts it, 'Opponents of progress understand they can "paper" a project to death in America.' * In the 19th and early 20th centuries, early forms of space exploration, namely, the building of space observatories, were typically privately financed and organised. In a sense, the state-dominated Space Economy of the mid-tolate 20th century was the exception, and the recent rise of private space entrepreneurs can be seen as a return to the historic norm.
Keywords: 330; Space; Space technology; Space science; Space travel; Weltraum; Weltraumtechnik; Weltraumwissenschaften; Raumfahrt